ERK2 Is a Promoter of Cancer Cell Growth and Migration in Colon Adenocarcinoma - Alessia Parascandolo; Giulio Benincasa; Francesco Corcione; Mikko O. Laukkanen (MDPI AG, 2024)
ERK1/2 phosphorylation is frequently downregulated in the early phase of colon tumorigenesis with subsequent activation of ERK5. In the current work, we studied the advantages of ERK1/2 downregulation for tumor growth by dissecting the individual functions of ERK1 and ERK2. The patient sample data demonstrated decreased ERK1/2 phosphorylation in the early phase of tumorigenesis followed by increased phosphorylation in late-stage colon adenocarcinomas with intratumoral invasion or metastasis. In vitro results indicated that SOD3-mediated coordination of small GTPase RAS regulatory genes inhibited RAS-ERK1/2 signaling. In vitro and in vivo studies suggested that ERK2 has a more prominent role in chemotactic invasion, collective migration, and cell proliferation than ERK1. Of note, simultaneous ERK1 and ERK2 expression inhibited collective cell migration and proliferation but tended to promote invasion, suggesting that ERK1 controls ERK2 function. According to the present data, phosphorylated ERK1/2 at the early phase of colon adenocarcinoma limits tumor mass expansion, whereas reactivation of the kinases at the later phase of colon carcinogenesis is associated with the initiation of metastasis. Additionally, our results suggest that ERK1 is a regulatory kinase that coordinates ERK2-promoted chemotactic invasion, collective migration, and cell proliferation. Our findings indicate that ROS, especially H2O2, are associated with the regulation of ERK1/2 phosphorylation in colon cancer by either increasing or decreasing kinase activity. These data suggest that ERK2 has a growth-promoting role and ERK1 has a regulatory role in colon tumorigenesis, which could lead to new avenues in the development of cancer therapy.